Creating Blogs with Jekyll - Dhillon, Vikram (Apress : Imprint: Apress, 2016)
Learn to create your own blog using the Jekyll static site generator. You'll start with a simple template, add new features to it, automate any maintenance, attach social sharing, and begin writing. By the end of Creating Blogs with Jekyll, you will be able to create custom blogs with Jekyll, update the content with ease, and reach out to your readers with minimal effort. Because you've built your blog yourself, you'll know exactly how each component works, and you won't be dependent on an admin panel to maintain it. Creating Blogs with Jekyll equips you with the knowledge to create an elegantly designed blog and scale it to capture more readers. Recapture the magic of writing by creating great content and use an easy workflow in Jekyll to maintain it for blogging. Do new things and write about them in style with Jekyll. Takes you through building a fully functional blog from scratch using Jekyll Provides a fun way to work on a side-project and integrate cutting edge web technologies Teaches you how to update and maintain your awesome blog Jekyll is a simple, secure and very low maintenance blog engine that converts naturally written content in markdown into a beautiful and minimal blog. It allows you to focus on content creation and expressing yourself instead of spending all your time updating the plugins and maintaining the database. Jekyll does not rely on a database as a backend so your blog will be far more secure and reliable than any traditional blogging engines such as WordPress.